THE UNCONSCIOUS MEMORIES OF LOSING AS THE TRIGGER FACTOR OF SELF DEFENSE MECHANISMS IN THE NOVEL PLEASE LOOK AFTER MOM BY KYUNG-SOOK SHIN - Manik, Indah Novelina; Hafsah, Siti (Faculty of Letters Universitas Balikpapan, 2024)
This research explores the unconscious that is reflected in the unconscious memories of loss in the novel Please Look After Mom by Kyung-Sook Shin. There are two objectives of this research: 1) To find out the form of unconscious memory contained in the novel